Prehospital trauma death review in the State of Victoria, Australia: a study protocol - Mercier, Eric (BMJ Open, 2018)
INTRODUCTION: Regionalised trauma systems have been shown to improve outcomes for trauma patients. However, the evaluation of these trauma systems has been oriented towards in-hospital care. Therefore, the epidemiology and care delivered to the injured patients who died in the prehospital setting remain poorly studied. This study aims to provide an overview of a methodological approach to reviewing trauma deaths in order to assess the preventability, identify areas for improvements in the system of care provided to these patients and evaluate the potential for novel interventions to improve outcomes for seriously injured trauma patients. METHODS AND ANALYSIS: The planned study is a retrospective review of prehospital and early in-hospital (<24 hours) deaths following traumatic out-of-hospital cardiac arrest that were attended by Ambulance Victoria between 2008 and 2014. Eligible patients will be identified from the Victorian Ambulance Cardiac Arrest Registry and linked with the National Coronial Information System. For patients who were transported to hospital, data will be linked the Victoria State Trauma Registry. The project will be undertaken in four phases: (1) survivability assessment; (2) preventability assessment; (3) identification of potential areas for improvement; and (4) identification of potentially useful novel technologies. Survivability assessment will be based on predetermined anatomical injuries considered unsurvivable. For patients with potentially survivable injuries, multidisciplinary expert panel reviews will be conducted to assess the preventability as well as the identification of potential areas for improvement and the utility of novel technologies. ETHICS AND DISSEMINATION: The present study was approved by the Victorian Department of Justice and Regulation HREC (CF/16/272) and the Monash University HREC (CF16/532 – 2016000259). Results of the study will be published in peer-reviewed journals and reports provided to Ambulance Victoria, the Victorian State Trauma Committee and the Victorian State Government Department of Health and Human Services.